Implementation of Regional Asset Management Policies at Office of Theduripoku District in Pasangkayu Regency - Safri, Safri; Hasbullah, Hasbullah; Suasa, Suasa (Journal of Progressive Law and Legal Studies, 2024)
The results of the research the implementation of asset management policies at the Duripoku District Office, Pasangakyu Regency is quite good but there is still something lacking namely the implementation of Regional Asset Management policies at the Duripoku District Office, Pasangkayu Regency, from the aspect of the organizational structure, it is running well, this is proven by the existing implantation, seen from the inventory of goods which is also carried out by data collection and labeling, from the resource aspect, the implementation of the Regional asset management policy at the Duripoku District Office, Pasangkayu Regency, is considered to be still lacking or not yet implemented optimally. This is indicated by the absence of trained personal in terms of ability or competency possessed by property managers, in addition to that, financial resources or budgets are considered to still be insufficient to support this implementation as well as inadequate facilities and infrastructure, from the aspect of communication, implementation of regional asset management policies in Duripoku District Office Pasangkayu Regency, is considered to have been implemented or implemented and conveyed rather via Whatsapp or other media to all stakeholders involved through socialization and coordination, so that the delivery of this asset management policy is carried out clearly regarding the entire process of regional property assets, stratifying from controlling goods, inventory assessment, utilization, regional property, transfer, administration and even securing regional property, as well as the delivery of this policy is always carried out consistently with the relevant stakeholders, in this case it is intended that the implementation of this rule can be carried out properly as it should.